Perancangan Jaringan Lte-Advanced Menggunakan Metode Carrier Aggregation Intra Band Non-Contiguous Di Kabupaten Kampar - Sihotang, Hari; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
LTE-Advanced is the latest technology as an evolution of LTE and expected to be able to provide efficient services in the use of spectrum. So it can provide higher data rate speeds both on the downlink side and on the uplink side. Carrier Aggregation (CA) is a Method on technology at LTE-Advanced, and with this Carrier Aggregation, it can add value to throughput on the customer side by utilizing the available spectrum. In Kampar Regency all areas have not been reached by the LTE network. There is no application of LTE-Advanced technology in the Kampar district. The purpose of this research is to improve the better service performance needed by LTE-Advanced users by using the Carrier Aggregation Method. The design of the carrier aggregation method obtained 99.79% coverage by signal at the signal level ≤ -80 dBm which almost reached the entire planning area very well. After the design of LTE-Advanced with the Carrier Aggregation Method, the number of sites needed is 320 sites to cover all the required planning areas.Keywords: LTE-Advanced, Carrier Aggregation, signal level.